Concepções de acompanhantes de pacientes com câncer de mama sobre o acolhimento da equipe multiprofissional em âmbito hospitalar - SILVA, Carla Steffane Oliveira e (2019)
The number of women with breast cancer increases considerably each year and their diagnosis and therapeutic process represent an emotional overload for the patient and a family, and it is up to the multiprofessional team to innovate in their interaction and reception proposals. With this research and analysis as conceptions of the companions of patients with breast neoplasia, regarding the reception of information by multiprofessional team in hospital languages. This was a qualitative, cross-sectional, descriptive study, carried out in a Center of High Complexity in Oncology - CACON, reference in cancer treatment in the state of Pará. The subjects of the study were followers of patients diagnosed with breast tumor, hospitalized for treatment and clinical follow-up. As researches have shown tools that demonstrate the importance of the host to the companion, which should be observed as a device of great value to meet the requirements of access to health services, as well as the best market for professionals and professionals. However, it was evidenced as repercussions generated by the mammary neoplasia to the family dynamics, ratifying an important one of the support to the relatives of patients with breast cancer, given the impacts generated to the nucleus of family diagnosis and of the therapeutic process, as well as the importance of the familiar representation and its insertion.